Kearifan Lokal Pendukung Kerukunan Beragama pada Komuntias Tengger Malang Jatim - Joko Tri Haryanto (Balai Penelitian dan Pengembangan Agama Semarang, 2014)
AbstractReligious harmony is an important prerequisite for Indonesian nation to implement national development. The model of religious harmony can be found in traditional wisdom which take the form of norms or practical traditions. This study aims to reveal the indigenous wisdom of Tengger community in the village Ngadas of Malang district in building religious harmony. The research used case study approach. The research reveals that the Tengger community in the village Ngadas was multi-religious people: Buddhist, Muslims, and Hindus. They all are able to maintain harmony and religious harmonythrough various traditions and customary norms of Tengger. Religious harmony is reflected in the tradition of gentenan (a tradition of helping each other) sayan (invitation to attend a certain celebration), Genten cecelukan or gentenan nedha (inviting each other to have dinner), nglayat or nyelawat (helping neighbors who expressed difficulties) andso on. The tradition is constructed by local knowledge that people need each others. That is why they should help other people. The tradition implies harmony folk wisdom to help each other because they recognize the need for the support of others themselves.Keywords: local wisdom, Tengger community, harmony AbstrakKerukunan beragama menjadi prasyarat penting bagi Bangsa Indonesia untuk melakukan pembangunan. Model kerukunan beragama dapat ditemui pada kearifan lokal masyarakat dalam berbagai bentuk tradisi dan norma sosial. Penelitian inibertujuan untuk mengungkapkan kearifan lokal Komunitas Tengger di Desa Ngadas Kabupaten Malang dalam membangun kerukunan beragama. Penelitian yang dilakukan dengan pendekatan studi kasus ini mengungkapkan komunitas Tengger di Desa Ngadasyang multi-agama yaitu Buddha, Islam, dan Hindu mampu memelihara kerukunan dan keharmonisan beragama melalui berbagai tradisi dan norma adat Tengger. Kerukunan beragama ini tercermin dalam tradisi gentenan (saling bergantian) untuk membantu hajatan sesama warga, sayan (undangan hajatan), genten cecelukan atau gentenannedha (bergantian mengundang makan), nglayat atau salawatan (membantu tetangga yang kena musibah). Tradisi tersebut terbentuk dari pengetahuan lokal mereka bahwa setiap orang membutuhkan bantuan orang lain oleh karena itu mereka pun harusbersedia membantu orang lain.Kata kunci: kearifan lokal, Tengger, kerukunan